Nicolas Brisset, Performativité des énoncés de la théorie économique : une approche conventionnaliste - Nicolas Brisset (Revue de la Régulation)
This thesis explores the analytical scope offered by the notion of performativity of economics. After having emphasize that its principal limit was its difficulty of provide a clear theorization of potential failures of performativity, we set a new approach of this idea based on the concept of convention: to perform the social world, a theory must become a new convention in an existing social world made of conventions. I then use this new conceptual frame in case-studies.